The Impact of Old Age Allowance on Elderly People’s Socio-Economic Life: A Study of Kumal Community in Lamjung - Sedhai, Gopal Prasad (Prithvi Journal of Research and Innovation, 2020)
This study focuses on the response of elderly people on the old age allowance and its impact on socio-economic issues. The allowance is the cash provided by the government of Nepal as a social security allowance to the people of age 70 years and above. Both qualitative and quantitative data has been used in this study from complete enumeration. The information was collected from three municipalities: Sundar Bazar Municipality, Maddhye Nepal Municipality, and Rainas Municipality of Lamjung District. A face-to-face interview method was applied to collect information regarding social and economic aspects from all 51 elderlies of Kumal respondents who received allowance. Chi-square test was applied to find out the factors associated with satisfaction of elderly people. Most of the respondents felt that the allowance is negligible and administrative difficulties like error in date of birth in citizenship, delay in receiving, inaccessibility to bank due to ageing, etc. in receiving the allowance. People who were satisfied with this allowance reported that it was a privilege from the government and they can use this money on their own. This finding is based on a single ethnic group of small area and cannot be generalized to whole population but explored some idea how the allowance is perceived in Nepal. The allowance establishes the right of older people and essential for poor people to fulfil their daily needs. The government should take some initiatives for better management of the allowance with other processes rather than cash distribution and take more initiation for very poor older people who have no other income sources.